Working Digital Money into a Cash Economy - O'Neill, Jacki; Dhareshwar, Anupama; Hulikal Muralidhar, Srihari (Microsoft, 2017)
This is a near final version of the publication, to quote this please refer to the final version O’Neill, Jacki, Anupama Dhareshwar, and Srihari H. Muralidhar. "Working Digital Money into a Cash Economy: The Collaborative Work of Loan Payment." Computer Supported Cooperative Work (CSCW) 26, no. 4-6 (2017): 733-768. Published by Springer. Abstract. This paper examines how different forms of money, specifically digital versus cash, impact on the work of an organisation and its customers. In doing so it contributes to the body of literature exploring the relationship between the social meanings of money and practice. We conducted an ethnographic study of loan collections; specifically, the workflows whereby a social enterprise intermediary managed the loans given to auto-rickshaw drivers to purchase their auto-rickshaws. Drivers made payments in cash or through mobile money. We found that making the mobile money service usable for the drivers took considerable work. It is tempting to take a transactional approach to payments, and indeed we initially approached the problem of enabling frequent payments as one of payment mechanism. However, in practice, payments take place within sets of social relations and, in this case, usability was achieved because the mobile payment system was embedded in a wider, trusted, loan payment ecosystem. It takes considerable collaborative work, and a fair amount of flexibility, to enable these financially vulnerable drivers to pay off their loans, and reducing the issue to one of payment mechanism alone does not tell the full story.